2012
DOI: 10.3109/09638288.2012.702848
|View full text |Cite
|
Sign up to set email alerts
|

Sensibility assessment of the HIV Disability Questionnaire

Abstract: • As people with HIV infection live longer, individuals may face a range of health-related challenges due to the disease, concurrent health conditions and the potential adverse effects of treatment. Together, these health-related challenges may be termed disability. • The HIV Disability Questionnaire (HDQ) is the first HIV-specific instrument developed to describe the presence, severity and episodic nature of the disability experienced by adults living with HIV. The HDQ is comprised of four domains including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…In addition to comments on face and content validity, format, and ease of usage, participants provided insightful recommendations for future HDQ revision to increase its applicability and feasibility for use in research and clinical settings. Results of the sensibility assessment are published elsewhere (O'Brien et al, 2013). Our focus in this article is to describe the strengths and challenges of our qualitative team-based approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to comments on face and content validity, format, and ease of usage, participants provided insightful recommendations for future HDQ revision to increase its applicability and feasibility for use in research and clinical settings. Results of the sensibility assessment are published elsewhere (O'Brien et al, 2013). Our focus in this article is to describe the strengths and challenges of our qualitative team-based approach.…”
Section: Resultsmentioning
confidence: 99%
“…Specific objectives are to (1) present our team approach to data collection and qualitative directed content analysis (methods) and (2) discuss the strengths and challenges associated with this approach (results and discussion). Rather than present the sensibility assessment findings of the HDQ, which are published elsewhere (O'Brien et al, 2013), our primary focus is to describe our process of using a qualitative team approach for directed content analysis of interview data. By providing a detailed account of our methodological process, other researchers will be better informed to consider this approach when assessing the sensibility of a newly developed questionnaire.…”
Section: Purpose and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier assessment of HDQ sensibility, adults living with HIV and clinicians who work in HIV care supported the term ''disability'' representing the construct of interest in the HDQ. Disability collectively represented the health-challenges defined by adults living with HIV described in the Episodic Disability Framework [18].…”
Section: Hiv Disability Questionnaire (Hdq)mentioning
confidence: 99%
“…Development of a new questionnaire requires multiple stages of comprehensive and rigorous assessment and refinement. We previously demonstrated that the HDQ has face and content validity and is easy to use with adults living with HIV [18]. However, the true domains of disability (or scoring structure) of this instrument was unknown.…”
Section: Introductionmentioning
confidence: 98%